The Maryland Contraceptive Equity Act (MCEA): Provider Awareness and Impact on Contraception Provision [35I]. (May 2020) - Cheedalla, Aneesha; Lee, Jessica; Burke, Anne E.
Abstract : INTRODUCTION: The Maryland Contraceptive Equity Act (MCEA) took effect in January 2018, with the goal of reducing barriers to contraception among insured individuals. Key provisions allow 12-month supplies/prescriptions of short-acting contraception and remove prior-authorization requirements for long-acting reversible contraception (LARC). We sought to assess MCEA impact on contraceptive provision in Maryland. METHODS: From March-June 2019, we emailed an Institutional Review Board-approved survey to Obstetrics/Gynecology (OBG), Internal Medicine (IM), Pediatrics, and Family Medicine (FM) providers throughout Maryland. The 24-item survey queried provider's prior awareness of the MCEA, changes to counseling, prescribing, and administrative practices based on the MCEA prior to the survey, likelihood of changes after MCEA awareness, changes in prior-authorization requirements for LARC, and MCEA impact on contraception access. Responses utilized a 5-point Likert scale (1: Very unlikely – 5: Very likely). RESULTS: The survey was sent to 1256 providers with 164 responses (13%): 67 OBG, 53 IM, 22 Pediatrics, 22 FM. One-hundred fourteen (70%) providers were unaware of the MCEA. The mean score of likelihood that the MCEA would change contraceptive counseling was 3.4/5 (SD 1.30), prescribing practices 3.5/5 (SD 1.29), and administrative practices 3.2/5 (SD 1.27). Of providers offering LARC, 22/42 (52%) reported fewer prior-authorization requirements since MCEA enactment. Fifty-eight percent of providers thought the MCEA very likely to increase access to LARC and 40% rated it very likely to increase access to short-acting contraceptives. CONCLUSION: Most contraceptive providers were not aware of MCEA provisions, but report that with increased awareness, their contraceptive counseling and prescribing practices are likely to change.